Genomic approaches for studying craniofacial disorders. Issue 4 (18th October 2013) - Khandelwal, Kriti D.; van Bokhoven, Hans; Roscioli, Tony; Carels, Carine E.L.; Zhou, Huiqing; Cox, Timothy C.; Luquetti, Daniela V.; Cunningham, Michael L.
Abstract Fast developing technologies in genomics have driven genetic studies of human diseases from classical candidate approaches toward hypothesis‐free and genome‐wide screening methods. Compared to the low‐resolution cytogenetic techniques that were the only available methods to visualize genomic changes at the chromosomal level until some 15 years ago, genome‐wide studies including analyses of copy number variation (CNV), genome‐wide association and linkage studies, and exome sequencing (ES) provide more accurate information for unraveling the genetic causes of diseases. Moreover, genome sequencing (GS) which interrogates the genome of a single individual at the nucleotide resolution has also been applied in genetic studies. Here we review genomic approaches in craniofacial disorders, with the emphasis on orofacial clefts, and discuss the applications, advantages, limitations, challenges, and future perspectives. © 2013 Wiley Periodicals, Inc.